2016
DOI: 10.4054/demres.2016.34.22
|View full text |Cite
|
Sign up to set email alerts
|

Differences in all-cause mortality

Abstract: BACKGROUNDDifferences in all-cause mortality between immigrants and host populations may provide insight into health inequities that could be reduced. OBJECTIVEDeath risks of adult immigrants were compared to those of the host population to assess effects of country of origin, duration of residence, calendar period, and sociodemographic characteristics, i.e., sex, education, and marital and parental status. METHODSRegistry data encompassing the entire Norwegian population age 25-79 in 1990-2012 were used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 56 publications
(69 reference statements)
2
13
0
1
Order By: Relevance
“…The hypothesis of the “healthy migrant” effect agrees with the main characteristics of the foreign-born population in Barcelona and other metropolitan areas of Spain [6]. However, over time, this protective effect may weaken, diminishing the relative advantage of migrants over locally/born people [20]. This could explain why, in our study, excess mortality appeared in foreign-born men in socioeconomically deprived neighborhoods in the last period studied.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The hypothesis of the “healthy migrant” effect agrees with the main characteristics of the foreign-born population in Barcelona and other metropolitan areas of Spain [6]. However, over time, this protective effect may weaken, diminishing the relative advantage of migrants over locally/born people [20]. This could explain why, in our study, excess mortality appeared in foreign-born men in socioeconomically deprived neighborhoods in the last period studied.…”
Section: Discussionsupporting
confidence: 82%
“…In addition, some studies analyzed how this pattern was mediated by sex, age and country of origin [11–17] and depended on the specific cause of death [11, 12, 1518]. Few studies have analyzed the association between immigrant mortality and greater length of residence [13, 19, 20]. A study has suggested that immigrant mortality may be influenced by different integration policy contexts in host countries [21].…”
Section: Introductionmentioning
confidence: 99%
“…Finding the best quality of communication using an interpreter is important to reduce miscommunication since language barriers are central risk factors in relation to healthcare for migrants (Hampers et al 1999;Bischoff 2003;Ramirez et al 2008;Bauer & Alegria 2010;Seffo et al 2014;Ventriglio et al 2014;Njeru et al 2015). Good quality of communication is very central to the health of migrated people (Leininger & McFarland 2006), since migration and integration can lead to positive or negative consequences for the health of the individual (Albin et al 2005;Wallace & Kulu 2014;Syse et al 2016). In order for elderly migrants in elderly healthcare to have equal living conditions, and for patients in healthcare, the quality of communication using interpreters is essential to manage to maintain regulations regarding respect, self-determination, human dignity, the feeling of well-being and participation in care and at the same time ensure equal care for migrants (SFS 2017:30;SFS 2014:821;SFS 2001: 453).…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…In health encounters it is of special importance for healthcare professionals to have access to good communication with possibilities to talk about the outcome of the person's migration process, since previous studies show that the migration process can have affected their health (Albin et al 2005;Syse et al 2016;Wallace & Kulu 2014).…”
Section: Language Barriers and Interpreting Practices In Healthcarementioning
confidence: 99%
See 1 more Smart Citation